Carbon dioxide purity and combustion characteristics of oxy firing compared to air firing in a pilot-scale circulating fluidized bed. (1st January 2019) - Moon, Ji-Hong; Jo, Sung-Ho; Park, Sung Jin; Khoi, Nguyen Hoang; Seo, Myung Won; Ra, Ho Won; Yoon, Sang-Jun; Yoon, Sung-Min; Lee, Jae-Goo; Mun, Tae-Young
Abstract: This study aims to optimize the oxy-circulating fluidized bed combustion (oxy-CFBC) process by reducing the amount of flue gas with high-purity carbon dioxide. To achieve this, the stable transition from air mode to oxy mode is tested and validated in a 0.1-MW oxy-CFBC test rig. The results prove that flue gas carbon dioxide separation can achieve 96 vol% (dry) through a stable transition from air mode to oxy mode. Moreover, flue gas production emitted in oxy mode is reduced to one fifth compared to air mode. The proven technologies and oxy-fuel combustion database from this test rig operating experience can be used as empirical operating parameters for the next steps such as demonstration and commercial-scale operation. Highlights: The oxy-circulating fluidized bed combustion (oxy-CFBC) process is optimaized with the flexible flue gas recirculation. High-purity-CO2 flue gas is achieved by stable transition from air firing to oxy firing. 0.1-MWth test results prove that flue gas CO2 separation achieves 96 vol% (dry). Optimal operating bed pressure drop conditions derived in oxy-CFBC.